Norwogonin attenuates hypoxia-induced oxidative stress and apoptosis in PC12 cells - Jing, Linlin (BMC Complement Med Ther, 2021)
BACKGROUND: Norwogonin is a natural flavone with three phenolic hydroxyl groups in skeletal structure and has excellent antioxidant activity. However, the neuroprotective effect of norwogonin remains unclear. Here, we investigated the protective capacity of norwogonin against oxidative damage elicited by hypoxia in PC12 cells. METHODS: The cell viability and apoptosis were examined by MTT assay and Annexin V-FITC/PI staining, respectively. Reactive oxygen species (ROS) content was measured using DCFH-DA assay. Lactate dehydrogenase (LDH), malondialdehyde (MDA) and antioxidant enzyme levels were determined using commercial kits. The expression of related genes and proteins was measured by real-time quantitative PCR and Western blotting, respectively. RESULTS: We found that norwogonin alleviated hypoxia-induced injury in PC12 cells by increasing the cell viability, reducing LDH release, and ameliorating the changes of cell morphology. Norwogonin also acted as an antioxidant by scavenging ROS, reducing MDA production, maintaining the activities of superoxide dismutase (SOD), catalase (CAT) and glutathione peroxidase (GPx), and decreasing the expression levels of HIF-1α and VEGF. In addition, norwogonin prevented cell apoptosis via inhibiting the expression levels of caspase-3, cytochrome c and Bax, while increasing the expression levels of Bcl-2 and the ratio of Bcl-2/Bax. CONCLUSIONS: Norwogonin attenuates hypoxia-induced injury in PC12 cells by quenching ROS, maintaining the activities of antioxidant enzymes, and inhibiting mitochondrial apoptosis pathway.